ADOLESCENCE TIBIAL TUBERCLE AVULSION FRACTURE: OPTION OF SURGICAL TREATMENT IN WORSENING CONDITION OF PRE-EXISTING OSGOOD-SCHLATTER DISEASE (OSD) - Fira Soraya; Ritzky Pratomo Affan; Bagus Danu Hariyanto (Universitas Airlangga, 2020)
Background: Osgood-Schlatter disease (OSD) is the most frequent cause of chronic knee pain in adolescents. Tibial tubercle avulsion fractures are an infrequent injury, approximately between 0.4-2.7% of all epiphyseal injury. Even though the relation between OSD and tibial tubercle avulsion fracture is still controversial, there are cases previously reported with this presentation.Case Report: A 16-years-old boy complained of pain on his left knee, significantly below the patella with ambulation limitation. He had a two-months history of knee pain in the same location and prominence on the area below the patella that was getting more significant over time. The patient was actively involved in volleyball in his school. The radiographic findings show fragmented tubercle fractures on the left tibial, soft tissue swelling in the tubercle's anterior side, and increased density of the infrapatellar fat pad. The patient underwent ORIF with screws. After a one-month post-surgery, the patient felt minimal pain when bending his left knee.Discussion: Male adolescents (12-15 years) and repetitive sprinting and jumping sports are the risk factors for OSD. About 90% of cases show a complete resolution, but some conditions make the OSD worse, such as low compliance at exercise avoidance. Surgery is rarely indicated for OSD, but in the condition of, even though very uncommon, tibial tubercle avulsion fracture, surgery gives a better outcome and resolution.Conclusion: All Osgood-Schlatter disease' patients should temporarily restrict sports activities to prevent tibial tubercle avulsion fractures.